Psychological well-being during COVID-19 lockdown: Insights from a Saudi State University’s Academic Community - Alfawaz, Hanan A. (J King Saud Univ Sci, 2021)
OBJECTIVES: Measures to control the on-going COVID-19 pandemic such as quarantine and social distancing, together with information overload about the sporadic spread of the disease have negatively impacted many individuals’ mental and psychosocial health. This study aimed to investigate the prevalence of self-reported mental health parameters and the coping mechanisms of employees and students in a Saudi State University. METHODS: An online survey in both Arabic and English was launched targeting students, staff and faculty of King Saud University from May 11 to June 6, 2020, the peak of Saudi Arabia’s nationwide lockdown. A total of 1542 respondents (726 males and 816 females) aged 20–65 years old participated. RESULTS: Majority of the respondents claimed to have suffered from anxiety (58.1%), depression (50.2%) and insomnia (32.2%) during the lockdown. On average, 65.3% respondents agreed that family bond strengthened during lockdown. Those in the highest quartile of family bonding score (Q4) were 41% [odds ratio (OR) and 95% confidence interval (CI) of 0.59 (0.39–0.87), p < 0.001] and 59% [OR 0.41 (CI 0.27–0.64), p < 0.001] were less likely to be anxious and depressed, respectively, even after adjusting for covariates. This independent and significant inverse association was more apparent in females than males. CONCLUSION: Self-reported acute mental health disorders were common within the academic community during the COVID-19 lockdown. Strength of family bonding as a coping mechanism was instrumental in preserving mental well-being, especially in females.